KAJIAN HUKUM MENGENAI PERAN DAN FUNGSI LEMBAGA PENJAMIN SIMPANAN DALAM MENJAMIN SIMPANAN NASABAH PERBANKAN - NUGROHO, ADRIYANTO ADHI; Sugianto, Sugianto (Jurnal Yuridis, 2015)
The role and function of Deposit Guarantee Institution (LPS) in securing the banking customers deposit is very important in banking because it can make custumers feel secure on their deposit and keep the banking system stable. The purpose of establishing LPS is not only to guarantee the customer's deposit and to actively and strongly keep the stabilization of banking system based on authority, however, it is also to protect the collapse banks